KONTRIBUSI TERJEMAH AL-QUR’AN TERHADAP WACANA ISLAM MODERAT DI INDONESIA: Studi Atas Terjemah Ayat-ayat Tentang Kerukunan Umat Beragama - Adib Adib (UIN Siber Syekh Nurjati Cirebon, 2018)
Entering the post-millennial era marked by increasingly uncontrolled flow of information, the question of harmony between religious people increasingly faces strong challenges. For Indonesian Muslims, the bases of harmony have actually been contained in the Qur'an. However, they gain more understanding of the Scriptures through translated works. No fewer than 20 Al-Qur'an translation works in Indonesian and regional languages have circulated since the beginning of the twentieth century. In fact, the controversy regarding the meaning of various verses in translation is difficult to avoid and can trigger problems of religious harmony, even tending to be contrary to the discourse of moderate Islam which is characteristic of Islam in this country. This article examines some of the rich translations of the Koran in translating verses related to religious harmony as well as contributing to the translation of the Qur'an's work on the discourse of moderate Islam and religious harmony in Indonesia.